Sedative Agents, Synthetic Torpor, and Long-Haul Space Travel—A Systematic Review - Thomas Cahill; Nataliya Matveychuk; Elena Hardiman; Howard Rosner; Deacon Farrell; Gary Hardiman (Life)
Background: With renewed interest in long-duration space missions, there is growing exploration into synthetic torpor as a countermeasure to mitigate physiological stressors. Sedative agents, particularly those used in clinical anesthesia, have been proposed to replicate aspects of natural torpor, including reduced metabolic rate, core temperature, and brain activity. Objectives: This systematic review aims to evaluate the potential of sedative agents to induce torpor-like states suitable for extended spaceflight. The review specifically investigates their pharmacokinetics, pharmacodynamics, and performance under space-related stressors such as microgravity and ionizing radiation. Methods: We conducted a comprehensive search across multiple databases (e.g., PubMed, Scopus, Web of Science) for studies published from 1952 to 2024. Eligible studies included experimental, preclinical, and clinical investigations examining sedative agents (especially inhalation anesthetics) in the context of metabolic suppression or space-relevant conditions. Screening, selection, and data extraction followed PRISMA guidelines. Results: Out of the screened records, 141 studies met the inclusion criteria. These were thematically grouped into seven categories, including torpor physiology, anesthetic uptake, metabolism, and inhalation anesthetics. Sedative agents showed variable success in inducing torpor-like states, with inhalation anesthetics demonstrating promising metabolic effects. However, concerns remain regarding delivery methods, safety, rewarming, and the unknown effects of prolonged use in space environments. Conclusions: Sedative agents, particularly volatile anesthetics, hold potential as tools for inducing synthetic torpor in space. Nevertheless, significant knowledge gaps and technical challenges persist. Further targeted research is required to optimize these agents for safe, controlled use in spaceflight settings.